If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-3(3x-4)+5=52
We simplify the equation to the form, which is simple to understand
2-3(3x-4)+5=52
Reorder the terms in parentheses
2+(-9x+12)+5=52
Remove unnecessary parentheses
+2-9x+12+5=+52
We move all terms containing x to the left and all other terms to the right.
-9x=+52-2-12-5
We simplify left and right side of the equation.
-9x=+33
We divide both sides of the equation by -9 to get x.
x=-3.6666666666667
| -3(x+8)-2(4x-3)=-7 | | -3=5v-5 | | Xlnx=6lnx | | x+3.5=9 | | (4f+5)-(-5f-40)=180 | | -94-x=-12x+49 | | 13x^2-16x=4 | | 4(k+5)=2(9t-2) | | 4(v-8)=-2v-26 | | 8x=-8x-7x | | xsquared+12=1 | | 2x^2=x+29 | | -7(v+4)+5(6-7v)=44 | | 5d+7x+6= | | -36-3x=64-8x | | 12-8-12= | | 5-3x/4=4 | | 66*10= | | 8x-(6x+7)=6x-47 | | ×/11=×/12-8 | | 6+8-78738+3837484849=0939v | | 5x-40=10x-50 | | 6x-7-x=17 | | 58800=P-(0.00917P) | | -12=m+1-6 | | -7x-33=-9x+25 | | x+.10=70 | | =14*2.8+21*4.2 | | 3(x-2)+5x=-2(x+3)+10x | | (5/2n=98-n | | 15y-10y-14=54.90 | | 195=-5x+5(6x+9) |